Acquiring Action Competence in Geography Education - Flath, Martina; Schockemöhle, Johanna (Journal of Geography Education, 2010)
So far, international competence research largely has focused on approaches to examine cognitive competence structures. The purpose of the planned study is to investigate both motivational and volitional aspects of geographical action competence in order to gain insights into how pupils acquire, develop and deepen geographical action competence in the broadest sense. To do so, we follow Heckhausen and Gollwitzer’s Rubicon model of action phases and the theory of action-oriented learning in order to model the structures of geographical action competence. The model will then be tested and evaluated in school participation projects for pupils of grades 9/10. The study is designed to provide empirically valid insights into the structure of the competence area "Action" in Geography education.